Feasibility of bone marrow sparing volumetric modulated arc therapy to spare active bone marrow in cervical and vaginal cancer patients: a retrospective dosimetric analysis. Issue 4 (19th July 2021) - Beavan, Michaela; Dundas, Kylie; Hudson, Felicity; Surjan, Yolanda; Lau, Annie; Deshpande, Shrikant; Lim, Karen; Do, Viet
Abstract: Introduction: Chemoradiotherapy (CRT) is the standard treatment for locally advanced cervical and vaginal cancer. It is associated with high haematological toxicity (HT) that can lead to treatment interruptions and cancelled chemotherapy cycles, reducing the potential effectiveness of this regimen. Bone marrow sparing (BMS) utilising volumetric modulated arc therapy (VMAT) is one method to reduce dose to the active bone marrow (ABM) so that HT rates are reduced. The aim of this paper was to assess whether BMS‐VMAT can effectively spare the ABM whilst maintaining clinically acceptable target and organ‐at‐risk (OAR) doses. Methods: Twenty gynaecological cancer patients treated with definitive CRT at the Liverpool/Macarthur Cancer Therapy centres between 2015 and 2020 were retrospectively included. ABM was delineated based on fluorodeoxyglucose positron emission tomography (FDG‐PET) imaging. Weekly blood tests and ABM dose parameters at the V10Gy, V20Gy, V30Gy, V40Gy and Dmean were assessed on original plans for any potential correlation with grade 2+ HT. Replanned with VMAT for BMS, various dose parameters were compared with the original plan to assess for any significant differences. Results: Active bone marrow doses were significantly reduced ( P  < 0.001 for all parameters) in BMS‐VMAT plans, and significant improvements in target and OAR coverage were found compared with the original plans. Compared with VMAT only, target and OARs were comparable. No significant correlations between HT and ABM doses were found. Conclusion: Bone marrow sparing volumetric modulated arc therapy can significantly reduce dose to the active bone marrow whilst maintaining acceptable target and OAR doses. Future prospective trials are needed to evaluate the clinical impact of BMS on toxicity and compliance. Abstract : Bone marrow sparing volumetric modulated arc therapy (BMS‐VMAT) is a recent technique aimed at reducing haematological toxicity in patients with cervical and vaginal cancer undergoing chemoradiotherapy that could potentially result in treatment interruptions. Our retrospective study found that significant dosimetric sparing in active areas of bone marrow could be achieved, whilst maintaining clinically acceptable target and organ‐at‐risk doses, comparable to VMAT where BMS was not considered.